Of the same breath Indigenous animal and place names - Möller, Lucie A. (UJ Press, 2017)
Of the Same Breath opens the door to a better understanding of why and how the animals and places of southern Africa have been given the names they have today. The vast reaches of the information provided in this book have been drawn together to create a veritable cornucopia of answers to the old question of how names originated. In this linguistically thought-provoking book, readers will be guided through the origins of animal names and toponyms, from the coastline of South Africa to the northern border of Namibia, and from the mighty elephant to the humble grasshopper.